Improving Teacher Performance in Developing Teaching ModulesBased on Kurikulum Merdeka through Academic Supervision - Mohsin Mohsin (Universitas Muhammadiyah Enrekang, 2023)
The subjects in this study were teachers of SMAN 15 Tanjung Jabung Barat, 2023/2024 academic year. There are 15 teachers at SMAN 15 Tanjung Jabung Barat. Of the 15 teachers, 11 teachers who teach in class X. Because the implementation of the Sekolah Penggerak program is only in class X. Activities are focused on 11 teachers who teach Class X with the Merdeka Curriculum. The difference in action in each cycle is in the type of use of supervision techniques. The academic supervision technique used in cycle I was a group technique, and in cycle II it was an individual technique through peer empowerment. If after two cycles the PTS objectives have not been achieved, the sub-techniques of the two techniques are used variably. The researcher can conclude that the performance of teachers at SMAN 15 Tanjung Jabung Barat in preparing Teaching Modules based on the Merdeka Curriculum is significantly improved through optimizing academic supervision with peer reinforcement. The implementation of individual techniques as an intensification of peer assistance is carried out in five steps applied by researchers to teachers whose performance is still low, or certain difficulties such as in the formulation of triggering sentences and assessments. In cycle II, the achievement of the MA section continued to increase. In the information section 97, then the core section reached 77, 80, 70, 63, and 77. The core competency section reached 70, 70, 80, 67, 67, 73, 70, and 87. The assessment section reached 70, 67, and 70. The enrichment section reached 70, 77. The reflection section reached 67 and 60. The appendix section reached 67, 73, and 63. Bibliography reached 73. The predicate in Cycle II no longer has the predicate not suitable, less suitable becomes 13%, the appropriate predicate appears at 87%.